What Are the Results of Limb Salvage Surgery for Primary Malignant Bone Tumor in the Forearm? - Liu, Weifeng; Yang, Yongkun; Jin, Tao; Sun, Yang; Li, Yuan; Hao, Lin; Zhang, Qing; Niu, Xiaohui (Frontiers in Oncology, 2022)
Background and Objectives: After diagnosing a primary bone tumor involving the forearm, various excision strategies and reconstruction methods must be considered. This study aims to explore the oncological and functional outcomes of limb salvage surgery for primary malignant bone tumors in the forearm. Methods: A total of 369 patients with primary forearm bone tumors were retrospectively analyzed between 2000 to 2017. There were 266 patients with radial tumors, and 46 (17.3%) were malignant, while 103 patients had ulnar lesions and 22 (21.4%) were malignant tumors. The oncological results, prognostic factors, and functional results after limb salvage surgery of forearm malignancies were analyzed. Results: The follow-up averaged 72.1 (7-192, median 62.5) months. Fifty-six patients who received limb salvage surgery were included in the final evaluation. Radius resection was performed in 38 patients, and distal radius (25 patients) was most frequent. Ulnar resection was performed in 18 patients, and proximal ulna (13 patients) was most frequent. The surgical margins obtained were intralesional in 3 patients, marginal in 8 patients and wide in 45 patients. Local recurrence occurred in 11 patients (19.6%), and distant metastasis occurred in 14 patients (25%). The 5-year recurrence-free survival rate was 79.8%. Unplanned excision, ulnar involvement, proximal forearm loocation and inadequate surgical margins were associated with recurrence. The overall 5-year and 10-year survival rates were 83.5% and 71.7%, respectively. Distant metastasis was a poor prognostic factor for survival rate. Forty-two patients were evaluated by MSTS score with an average of 27.9±1.5 . Conclusions: The incidence of radial malignant tumor is higher than that of ulnar lesions. The distal radius and proximal ulna are the most frequently involved sites. Unplanned excisions, ulnar tumors, proximal forearm tumors, and inadequate surgical margin are the risk factors for local recurrence. Distant metastasis is independent poor prognostic factors of death. The oncology control and functional results of limb salvage surgery were satisfactory.